Analysis of heavy metals in waters, sediments, and blood clams (Anadara granosa) in the pond at Sidoarjo Regency - Saputra, Andika Keessa; Sawiji, Asri; Maisaroh, Dian Sari (UIN Sunan Ampel Surabaya, 2023)
As industry continues to develop, both the oil and gas industry, agriculture and other non-oil and gas industries, the level of environmental pollution in Sidoarjo Regency is also increasing. Heavy metals are one of the pollutants in domestic waste and industrial waste which can affect river water quality and can have negative impacts on humans and the environment. The aim of this research is to determine the concentration of the heavy metals lead (Pb) and cadmium (Cd) in water, sediment and blood clam meat, determine the maximum consumption limit for the heavy metals Pb and Cd contained in blood clams, and determine relationship between Pb and Cd concentrations in waters, sediments and blood clams at research study, Tambak Cemandi and Banjar Kemuning station. The sampling method in this research used random sampling. Testing for heavy metals Pb and Cd uses Atomic Absorption Spectrophotometry (AAS). The research results showed that the concentrations of heavy metals Pb and Cd in the waters, sediments and blood clams at the research location had exceeded the established safe limits. Pearson correlation analysis showed that there was no significant relationship between Pb and Cd concentrations in waters, sediments and blood clams.